Impact of Artificial Elements on Mountain Landscape Perception: An Eye-Tracking Study - Suling Guo; Wei Sun; Wen Chen; Jianxin Zhang; Peixue Liu (Land, 2021)
The landscape is an essential resource for attracting tourists to a destination, but this resource has long been overused by tourism development. Tourists and scholars have begun noticing the interference of human structures in the natural environment and how this can change the meaning of a landscape. In this study, the impact of artificial elements on mountain landscapes was investigated by measuring the characteristics of visual perception and a landscape value assessment using eye-tracking analysis. Furthermore, this study includes socio-demographic features for testing whether they have an impact on landscape perception. The results show that human structures impact both visual perception and the perceived value of landscapes. Hotels and temples attract more visual attention than a purely natural landscape. Modern hotels appear to have a negative influence on mountain landscape valuation, while temples with unique culture have positive impacts. Socio-demographic groups differ significantly in how they observe landscape images and, to a degree, how they value the landscape therein. Our study should be of value to landscape planning and tourism policy making.